Aging effect on rheology and cracking behaviour of reclaimed binder with bio-based rejuvenators. (10th July 2018) - Cavalli, M.C.; Zaumanis, M.; Mazza, E.; Partl, M.N.; Poulikakos, L.D.
Abstract: Reclaimed asphalt pavement (RAP) is stiffer than the virgin material due to aging, thus it is expected to have worse cracking resistance. By adding bio-based rejuvenators, RAP binder mechanical performances at low temperatures improve: fracture toughness temperature of RAP decreases after the addition of rejuvenators to a level similar to the virgin binder. Furthermore, work to fracture of RAP binder increases after the addition of rejuvenators. Addition of rejuvenators to RAP binder can restore both mechanical properties and toughness at low temperature. However, despite the rejuvenators' addition, physio-chemical oxidation did not reverse as mechanical changes were not caused by chemical changes at functional groups level. Results confirmed how considering the effect of aging is crucial when studying how rejuvenators affect the RAP binder chemically and mechanically. Graphical abstract: Highlights: Fracture toughness transition temperature of RAP decreases after the addition of rejuvenators. After the addition of rejuvenators, work up to fracture of RAP improves. Bio-based rejuvenators are able to restore the mechanical properties of RAP binder. The viscoelastic characteristics depend on aging and can be influenced by RAP's rejuvenators. Mechanical changes due to rejuvenators were not caused by changes at chemical bonds/functional groups level.